Nanotechnology Interventions in the Management of COVID-19: Prevention, Diagnosis and Virus-Like Particle Vaccines - Balkrishna, Acharya; Arya, Vedpriya; Rohela, Akansha; Kumar, Ashwani; Verma, Rachna; Kumar, Dinesh; Nepovimova, Eugenie; Kuca, Kamil; Thakur, Naveen; Thakur, Nikesh; Kumar, Pankaj (Vaccines, 2021)
SARS-CoV-2 claimed numerous lives and put nations on high alert. The lack of antiviral medications and the small number of approved vaccines, as well as the recurrence of adverse effects, necessitates the development of novel treatment ways to combat COVID-19. In this context, using databases such as PubMed, Google Scholar, and Science Direct, we gathered information about nanotechnology's involvement in the prevention, diagnosis and virus-like particle vaccine development. This review revealed that various nanomaterials like gold, polymeric, graphene and poly amino ester with carboxyl group coated magnetic nanoparticles have been explored for the fast detection of SARS-CoV-2. Personal protective equipment fabricated with nanoparticles, such as gloves, masks, clothes, surfactants, and Ag, TiO2 based disinfectants played an essential role in halting COVID-19 transmission. Nanoparticles are used not only in vaccine delivery, such as lipid nanoparticles mediated transport of mRNA-based Pfizer and Moderna vaccines, but also in the development of vaccine as the virus-like particles elicit an immune response. There are now 18 virus-like particle vaccines in pre-clinical development, with one of them, developed by Novavax, reported being in phase 3 trials. Due to the probability of upcoming COVID-19 waves, and the rise of new diseases, the future relevance of virus-like particles is imperative. Furthermore, psychosocial variables linked to vaccine reluctance constitute a critical problem that must be addressed immediately to avert pandemic.
Keywords: virus-like particle vaccines; diagnosis; SARS-CoV-2; prevention; COVID-19